Assessing the Urban Design Features of Historical Street - Radha, Roza Abdullatif; Arif, Shallaw Sirwan; Ahmed, Zhalla Bahzad; Sharif, Faruq Baqi; Omer, Kawsar Adil; Ali, Awin Aziz (Kurdistan Journal of Applied Research, 2025)
This study offers a comprehensive and critical evaluation of the urban design elements of Goran Street, a central and historically significant artery in Sulaimani, located in the Kurdistan Region. The research focuses on four primary areas: the street’s physical characteristics, spatial organization, the utilization of open spaces, and its ability to meet user needs. Employing a mixed-methods approach—including field measurements, photographic documentation, on-site observations, and user questionnaires—the study reveals several critical deficiencies in urban design quality. Physically, Goran Street suffers from inconsistent building heights and architectural styles, leading to visual disunity. The chaotic use of building materials and color palettes further contributes to an aesthetically jarring environment. Pedestrian pathways are poorly maintained, with inadequate paving, signage, and street furniture, making the area less inviting for foot traffic. User-centered analysis reveals that Goran Street meets only 40.8% of the surveyed expectations related to accessibility, personal safety, and the availability of public services. Despite this, the frequency of open space usage remains high, with 75% of respondents indicating regular engagement, primarily due to the street’s central location, though the quality of these open spaces scores a concerning 0%. Additionally, the lack of cultural infrastructure, such as galleries, museums, or performance spaces, limits the street’s potential to serve as a cultural and tourism hub. The study concludes by calling for strategic interventions to enhance Goran Street’s urban appeal. Recommendations include improving walkability, redesigning public spaces, integrating cultural identity, and enforcing planning regulations to foster a vibrant, inclusive, and historically enriched urban environment.